Micro- and nanocellulose in polymer composite materials: a review - Omran, Abdoulhdi A. Borhana; Mohammed, Abdulrahman A. B. A.; S., M. Sapuan; R., A. Ilyas; M. R., M. Asyraf; Seyed Saeid, Rahimian Koloor; Petrů, Michal (MDPI, 2021)
The high demand for plastic and polymeric materials which keeps rising every year makes them important industries, for which sustainability is a crucial aspect to be taken into account. Therefore, it becomes a requirement to makes it a clean and eco-friendly industry. Cellulose creates an excellent opportunity to minimize the effect of non-degradable materials by using it as a filler for either a synthesis matrix or a natural starch matrix. It is the primary substance in the walls of plant cells, helping plants to remain stiff and upright, and can be found in plant sources, agriculture waste, animals, and bacterial pellicle. In this review, we discussed the recent research development and studies in the field of biocomposites that focused on the techniques of extracting micro- and nanocellulose, treatment and modification of cellulose, classification, and applications of cellulose. In addition, this review paper looked inward on how the reinforcement of micro- and nanocellulose can yield a material with improved performance. This article featured the performances, limitations, and possible areas of improvement to fit into the broader range of engineering applications.